Representasi Feminisme Postmodern pada Tokoh Tewkesbury dalam Film Enola Holmes (2020) - Belinda Purwanto Jahja; Sinta Paramita (Koneksi, 2026)
This study analyzes the representation of postmodern feminism through the character of Lord Tewkesbury in the film Enola Holmes (2020). The film is viewed as a cultural text that not only tells a story but also shapes and negotiates gender meanings through visual, verbal, and narrative signs. This research employs postmodern feminist theory using deconstructionist, poststructuralist, and performative approaches, which understand gender as a fluid social construct continuously formed through discourse. The analysis applies Roland Barthes’ semiotic framework of denotation, connotation, and myth. The study focuses on three key scenes that illustrate the reversal of gender roles, the negotiation of masculine identity within the social context of the Victorian era, and the performance of non-hegemonic gender expressions. The findings indicate that Tewkesbury is consistently portrayed as gentle, empathetic, reflective, and cooperative, thereby challenging dominant masculinity. These representations construct a myth of alternative masculinity that is more inclusive and humanistic, while emphasizing the role of popular media in expanding the understanding of gender as a dynamic spectrum in contemporary popular culture.     Penelitian ini menganalisis representasi feminisme postmodern melalui tokoh Lord Tewkesbury dalam film Enola Holmes (2020). Film dipandang sebagai teks budaya yang tidak hanya menyampaikan cerita, tetapi juga membentuk dan menegosiasikan makna gender melalui tanda visual, verbal, dan naratif. Penelitian ini menggunakan teori feminisme postmodern dengan pendekatan dekonstruksionis, poststrukturalis, dan performatif, yang memandang gender sebagai konstruksi sosial yang bersifat cair dan terus dibentuk melalui wacana. Analisis dilakukan dengan semiotika Roland Barthes yang mencakup denotasi, konotasi, dan mitos. Kajian ini menelaah tiga adegan kunci yang menunjukkan pembalikan peran gender, negosiasi identitas maskulinitas dalam konteks sosial era Victoria, serta performativitas gender non-hegemonik. Hasil penelitian menunjukkan bahwa Tewkesbury digambarkan sebagai sosok yang lembut, empatik, reflektif, dan kooperatif, sehingga menantang maskulinitas dominan. Representasi tersebut membangun mitos maskulinitas alternatif yang lebih inklusif dan humanis, serta menegaskan peran media populer dalam memperluas pemahaman gender sebagai spektrum yang dinamis dalam konteks budaya populer kontemporer secara luas masa kini.